Management of Initial HBV Therapy for an HBeAg-Negative Patient: A Case Discussion - Pan, MD, Calvin; Hu, MD, Ke-Qin (North American Journal of Medicine and Science, 2011)
A case study of a 45-year-old Chinese woman with chronic hepatitis B (CHB) diagnosed in 1999 …...